1997
DOI: 10.1071/s96040
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth promotion of wheat inoculated with Penicillium radicum sp. nov.

Abstract: A phosphate-solubilising isolate of Penicillium radicum (sp. nov.) was used to inoculate wheat (Triticum aestivum cv. Dollarbird) in a glasshouse experiment and a field trial, using low pH soils at 5 levels of phosphate application. When data for all phosphate application levels were combined, inoculation by P. radicum resulted in 14% increases in wheat yield in the field trial and increases in both phosphate uptake (10%) and yield (9%) in the glasshouse. In the glasshouse, the response to inoculation was high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(40 citation statements)
references
References 0 publications
2
36
0
2
Order By: Relevance
“…Use of P-solubilizing fungi in plant nutrition is well reported [28,29]. In the present study, the three fungal cultures exhibited their ability to enhance the growth of two crops.…”
Section: Discussionmentioning
confidence: 66%
“…Use of P-solubilizing fungi in plant nutrition is well reported [28,29]. In the present study, the three fungal cultures exhibited their ability to enhance the growth of two crops.…”
Section: Discussionmentioning
confidence: 66%
“…Combined nitrogen and phosphorus may be reflected in yield increase better than single treatments because these elements may affect the intake of each other. Whitelaw et al (1997) reported that combined treatment of phosphate-solubilizing and nitrogen-fixing bacteria increased P intake and promoted plant growth. Çakmakçı (2007) reported higher bacteria efficiency for combined inoculations.…”
Section: Discussionmentioning
confidence: 99%
“…Belimov et al (1995) also reported improved plant nutrient balance with combined treatments of phosphate-solubilizing and nitrogen-fixing bacteria. Phosphate-solubilizing Bacillus species promote growth through P nutrition (Banik and Ninawe, 1988;Whitelaw et al, 1997) and increase intake of other elements (Biswas et al, 2000). Çakmakçı et al (1999) reported that B. polymyxa and B. megaterium treatments increased kernel yield of barley respectively by 12.4% and 9.2% in sandy soils and by 17.1% and 7.8% in loamy soils, and combined inoculation increased yield by 17.0% in sandy and 19.4% in loamy soils.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorous-solubilizing microorganisms (PSM) are able to replenish soil solution P by solubilizing insoluble native and applied rock phosphate (Rao 1992;Gyaneshwar et al 2002b;Khan et al 2007). Although P-solubilizing bacteria (PSB) have received greater attention than P-solubilizing fungi (PSF), the latter are more effective in solubilizing P compounds (Kucey 1983;Whitelaw et al 1997). Moreover, PSF do not lose the P dissolving activities upon repeated subculturing under laboratory conditions as the PSB do (Kucey 1983;Rashid et al 2004).…”
Section: Introductionmentioning
confidence: 99%